Use of Both Fluoro-Jade B and Hematoxylin and Eosin to Detect Cell Death in the Juvenile Rat Brain Exposed to NMDA-Receptor Antagonists or GABA-Receptor Agonists in Safety Assessment. (July 2021) - Picut, Catherine A.; Mendes, Odete R.; Weil, David S.; Davis, Sarah; Swanson, Cynthia
Administration of pediatric anesthetics with N-methyl D-aspartate (NMDA)-receptor antagonist and/or γ-aminobutyric acid (GABA) agonist activities may result in neuronal degeneration and/or neuronal cell death in neonatal rats. Evaluating pediatric drug candidates for this potential neurotoxicity is often part of overall preclinical new drug development strategy. This specialized assessment may require dosing neonatal rats at postnatal day 7 at the peak of the brain growth spurt and evaluating brain tissue 24 to 48 hours following dosing. The need to identify methods to aid in the accurate and reproducible detection of lesions associated with this type of neurotoxic profile is paramount for meeting the changing needs of neuropathology assessment and addressing emerging challenges in the neuroscience field. We document the use of Fluoro-Jade B (FJB) staining, to be used in conjunction with standard hematoxylin and eosin staining, to detect acute neurodegeneration and neuronal cell death that can be caused by some NMDA-receptor antagonists and/or GABA agonists in the neonatal rat brain. The FJB staining is simple, specific, and sensitive and can be performed on brain specimens from the same cohort of animals utilized for standard neurotoxicity assessment, thus satisfying animal welfare recommendations with no effect on achievement of scientific and regulatory goals.